1996
DOI: 10.1200/jco.1996.14.9.2552
|View full text |Cite
|
Sign up to set email alerts
|

Delay in progression of bone metastases in breast cancer patients treated with intravenous pamidronate: results from a multinational randomized controlled trial. The Aredia Multinational Cooperative Group.

Abstract: At EMR, median time to PD in bone was increased by 48% in patients who received pamidronate (249 v 168 days; P = .02, Wilcoxon test). Marked pain relief, defined as a two-point decrease lasting for > or = 6 weeks, was reported by 44% of pamidronate patients and by 30% of controls (P = .025, chi 2 test). The infusions (median, nine per patient; range, 0 to 39) were well tolerated, with no major toxicities reported. Pamidronate by repeated infusion can significantly slow the progression of bone metastases and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
91
1
10

Year Published

1997
1997
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(103 citation statements)
references
References 19 publications
0
91
1
10
Order By: Relevance
“…The bisphosphonates, notably intravenous pamidronate (Purohit survival of 2.1 years et al, 1994;Conte et al, 1996;Hortobagyi et al, 1996) and to a lesser 0.001, Figure 5). This extent oral clodronate (Paterson et al, 1993), have been shown to patients subsequently relieve pain, reduce analgesic consumption and improve mobility.…”
Section: Discussion Chi= 1918mentioning
confidence: 99%
“…The bisphosphonates, notably intravenous pamidronate (Purohit survival of 2.1 years et al, 1994;Conte et al, 1996;Hortobagyi et al, 1996) and to a lesser 0.001, Figure 5). This extent oral clodronate (Paterson et al, 1993), have been shown to patients subsequently relieve pain, reduce analgesic consumption and improve mobility.…”
Section: Discussion Chi= 1918mentioning
confidence: 99%
“…Randomized trials in breast cancer patients have shown that bisphosphonate therapy in combination with either endocrine therapy or chemotherapy can significantly delay the onset of SREs and also reduce their frequency (25,(30)(31)(32)(33)(34). Moreover, in vitro studies have demonstrated that even though an increase in osteoclastic activity is considered to be the predominant mechanism for bone destruction, breast cancer deposits can directly resorb bone (17).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, four placebo-controlled trials (n ϭ 1,453) concluded that i.v. pamidronate (45-90 mg 3-4 weekly) results in a significantly longer time (12.7 versus 7.0 months; p Ͻ .001) to the occurrence of the first SRE (HR, 0.77; 95% CI, 0.69 -0.87), lower incidence of SREs (53% versus 68%; p Ͻ .001), and longer time to progression of bone lesions (8.3 versus 5.6 months; p ϭ .02) [21,[23][24][25][26][27]. Moreover, evidence from a head-to-head comparison suggests its superiority over clodronate in both controlling symptoms and suppressing bone resorption [28].…”
Section: Breast Cancermentioning
confidence: 99%